Effect of Polymeric Additives on the Performances of Polyethersulfone Blend Hollow Fiber Membrane - Bastian Arifin; Nasrul Arahman; Sri Mulyati; Yoshikage Ohmukai; Hideto Matsuyama (Syiah Kuala University, 2012)
The article reported the preparation and modification of hydrophobicpolyethersulfone (PES) by blending the solution with hydrophilic additives Tetronic 304, Tetronic 704, Tetronic 1307, and Tetronic 908. Polymeric porous membranes are generally prepared by the phase separation of polymer solution. In this work, we prepared hollow fibre membrane by non-solvent induced phase separation (NIPS). Effect of molecular weight of surfactant added on the performance and characteristic of fabricated membrane were investigated. The control PES membrane has the highest contact angle, indicating thelowest hydrophilic. With addition of surfactant Tetronic in the polymer blend hollow fibre membrane, the water contact angle decreased indicates that the membrane surface is more hydrophilic. Scanning electron microscopy (SEM) images for all of the membrane showed the structure of fibre with finger-like macro voids through the cross-section. The sponge-type of structure in the centre path of original membrane was disappearing with addition of Tetronic. Ultrafiltration experiment results showed that water permeability washighest with addition of Tetronic with lowest molecular weight. According to thecharacteristics of resulting membrane such as hydrophilicity, ultrafiltration performance, and pores structure, surfactant Tetronic was a good additive to produce hydrophilic membrane for drinking water application